'To Be That Self Which One Truly Is': Trans Experiences and Rogers' Theory of Personality. (2nd October 2022) - Crowter, Jay
ABSTRACT: In recent years, the question of what is best for trans individuals has been hotly debated. This paper takes Rogers' Theory of Personality and explores it alongside the experiences of trans individuals so as to add a Person-Centered perspective to the discourse. It is grounded in an understanding of the distress of not being oneself and explores in detail the barriers trans individuals can face on their journey to authenticity. Many of these barriers are societal attitudes that become internalized as conditions of worth. The most potent remedy to such conditions are the same for trans people as the rest of humanity: unconditional prizing, freedom to move in any direction and a trust in an individual as the expert in themselves. While many of us may apply these Rogerian attitudes to all our clients, there is no harm and great benefit to be found in explicitly reviewing them with regard to trans experiences. This paper reaffirms the great benefit of the person-centered approach in freeing us all to be more ourselves and reminds us of our responsibility to shape a society where everyone is afforded the greatest opportunity to live without conditionality or discrimination.